To A Complaint Crime Implementation of Sexual Violence of Husband to Wife in Polres Cirebon Jurisdictions - Yanto Irianto (Magister of Law, Faculty of Law, Universitas Islam Sultan Agung, 2018)
The smallest element of a country's society is the family. In the ship sailed home life husband and wife, conflicts between husband and wife which can lead to legal consequences. One of the conflicts in the home that can lead to the legal consequences of sexual violence husbands against wives. During this time, in case of sexual assault on a particularly husbands against wives, most victims of violence choose to divorce, few victims are willing to bring a criminal case is processed. The application to a complaint of a criminal offense of sexual violence is seen by some experts as a barrier to criminal law enforcement against criminal acts of domestic violence.The method used in this research is normative juridical. The results showed that a complaint of the victim is an absolute condition that must exist in the criminal justice process either under investigation or under prosecution in the case Sexual violence husband to wife. Complaints of victims is the most important thing in a crime that qualifies to a complaint. Without complaint the victim, the criminal justice process will not run.Keywords: Complaints Offense; Elimination; Sexual Violence.